Earnings Management by Firms in the SEC’s Pilot Program - Hua, Meiying; Skomra, Justyna; Alam, Pervaiz (Journal of Accounting, Business and Management (JABM), 2024)
Purpose: Using a sample of firms selected in a pilot program of the SEC Regulation SHO, we investigate whether managers make trade-off decisions between accrual-based earnings management and real activities manipulation over the period 2000-2015.Design/methodology/approach: Real activities manipulation is computed based on Roychowdhury (2006), and discretionary accruals are measured by modified Jones (1991) model. To examine trade-off decisions, we follow models developed by Zang (2012). Findings: We find that managers of pilot firms do not make strong sequential decisions about the use of accrual-based earnings management (ABEM) versus real activities earnings management (RAEM) and their decisions are not fully dependent on the relative costliness of earnings management.Originality: While prior studies provide evidence on short-selling firms and accrual management, no prior study has examined trade-off decisions between RAEM and ABEM for pilot firms, particularly during the pilot program.